Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Relative summer temperature changes from glacial fluctuations in the Scoresby Sund region, Central East Greenland, during late-glacial time - Meredith A. Kelly; Thomas V. Lowell; Brenda L. Hall; Laura B. Levy; Colby A. Smith; Katherine Salamido; Roseanne Schwartz; Jennifer A. Howley (Quaternary Science Reviews, 2025)

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Utilization of Fish Meal and Fish Oil from Smoked Salmon By-Products in Juvenile Striped Bass (Morone saxatilis) Feeds: Growth Performance, Nutritional Composition, and Shelf-Life Assessment of Upcycled Ingredients - Connor Neagle; Michael O. Frinsko; Ryan Kelly; Steven G. Hall; Benjamin J. Reading; Alexander Chouljenko; Greg Bolton; Michael Joseph (Fishes, 2025)
Fish meal (FM) and fish oil (FO) are vital components commonly used in feed formulations. However, their supply, which generally comes from capture fisheries, is being exhausted, necessitating the exploration of sustainable alternatives. In a two-part study, the first part evaluated the FM and FO derived from smoked salmon by-product (SSBP) over a 12-week accelerated shelf-life test, comparing their lipid oxidation, amino acid, and fatty acid profiles to those of commercial whitefish meal and oil. In the second part, the SSBP FM and FO were then included in three experimental feeds at 25%, 50%, and 100% inclusion levels. These feeds were tested on juvenile striped bass (Morone saxatilis) cultured in a recirculating aquaculture system (RAS). The results indicated that the quality of SSBP FM and FO was lower than the commercial product (less amino acids (23.98% vs. 60.30%) and omega-3 fatty acids (9.46% vs. 26.6%), respectively). SSBP FO exhibited high initial peroxide value (21.00 ± 0.00 meq/kg oil), with gradually increasing total oxidation value and p-Anisidine value during storage. Regarding the feeding trial, all fish showed signs of Mycobacterium marinum infection after one month. While there was no significant difference in feed palatability (p > 0.8559), the feed conversion ratio was less efficient for the 100% SSBP feed (1.44 ± 0.14) compared to commercial feed (1.36 ± 0.13), but these differences were not statistically significant. This study suggests that SSBP FM and FO can be used as supplements at lower levels (25% and 50%) without negatively affecting growth, feed efficiency, or survival. Our findings may be useful for enabling beneficial collaborations between smoked salmon processors, feed manufacturers, and striped bass farmers, therefore contributing to sustainability in aquaculture practices.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Influence of extruded soybean meal with different fat contents and varying oleic acid content on floating fish feed quality and composition - Danny B. Patiño; Ondulla T. Toomer; Thien C. Vu; Edgar O. Oviedo-Rondon; Rouf Mian; Mike Frinsko; Steven Hall; Ryan Kelly; Jason Mann; Michael Joseph (Animal Feed Science and Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Post-release survival of loggerhead sea turtles (Caretta caretta) incidentally hooked in a North Atlantic pelagic longline fishery - Michael C. James; Kelly E. Hall; Emily P. Bond; Scott Sherrill-Mix; Virginie Plot (Frontiers in Marine Science, 2024)
Estimating mortality of sea turtles incidentally captured in fishing gear is essential to understanding fishery impacts on sea turtle populations. Loggerhead turtles ( Caretta caretta ) are a component of bycatch in pelagic longline fisheries, including those operating in Atlantic Canada. In this study, we used pop-up satellite archival tags (PSATs) attached to 62 loggerhead turtles incidentally hooked in Atlantic Canadian shallow-set pelagic longline gear (2012–2018) to estimate associated post-release survival. Consistent with conventional fishing practices, hooks were not removed from turtles prior to release. Analysis of diving behaviour, ocean temperature, and ambient light level was used to assign fates to turtles. Post-release survival was calculated using the Kaplan-Meier estimator with right censoring. Based on this method, the annual survival probability of an individual loggerhead post-release is 0.877 ± SE 0.052. While it is commonly assumed that hook location is an important variable in predicting fates of turtles after release, there was no difference in survival of deep-hooked (swallowed hook) versus shallow-hooked turtles. These results indicate higher survivorship among hooked loggerheads captured in shallow-set pelagic longline gear than prevailing wisdom and suggest that at least some of the population impacts on loggerhead turtles conventionally attributed to pelagic longline interactions may be linked to other threats.

Diagnosis and treatment of an oral, migrating foreign body penetrating the spinal cord in a rabbit (Oryctolagus cuniculus) - Margaret Cook; Amanda L. Day; Catriona MacPhail; Becky Pacheco; Anna Price; Camilla Cooper; Kelly Hall; Alex Ohlendorf; Miranda J. Sadar (Journal of Exotic Pet Medicine, 2024)

Understanding perceptions of tumor genomic profile testing in Black/African American cancer patients in a qualitative study: the role of medical mistrust, provider communication, and family support - Caseem C. Luck; Sarah Bauerle Bass; Yana Chertock; Patrick J. A. Kelly; Katie Singley; Ariel Hoadley; Michael J. Hall (Journal of Community Genetics, 2024)

Hurricane Effects on Seagrass and Associated Nekton Communities in the Northern Gulf of Mexico - Kelly M. Correia; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Darnell; M. Zachary Darnell; Bradley T. Furman; Margaret O. Hall; Christian T. Hayes; Charles W. Martin; Ashley McDonald; Delbert L. Smee (Estuaries and Coasts, 2024)

Short-stature and tall maize hybrids have a similar yield response to split-rate vs. pre-plant N applications, but differ in biomass and nitrogen partitioning - Kevin R. Kosola; Magen S. Eller; Frank G. Dohleman; Lia Olmedo-Pico; Brad Bernhard; Eric Winans; Ty J. Barten; Lillian Brzostowski; Lesley R. Murphy; Chiyu Gu; Lyle Ralston; Mike Hall; et al. (Field Crops Research, 2023)

The mane factor: Compliance is associated with increased hair cortisol in the horse - Aurélie Jolivald; Carrie Ijichi; Carol Hall; Kelly Yarnell (Applied Animal Behaviour Science, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Environmental Drivers of Seagrass-Associated Nekton Abundance Across the Northern Gulf of Mexico - Benjamin A. Belgrad; Kelly M. Correia; Kelly M. Darnell; M. Zachary Darnell; Christian T. Hayes; Margaret O. Hall; Bradley T. Furman; Charles W. Martin; Delbert L. Smee (Estuaries and Coasts, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Holocene climate and environmental history of East Greenland inferred from lake sediments - Amanda R. Lusas; Brenda L. Hall; Thomas V. Lowell; Meredith A. Kelly; Ole Bennike; Laura B. Levy; William Honsaker (Journal of Paleolimnology, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

Reduction of fumarate, mesaconate and crotonate by Mfr, a novel oxygen‐regulated periplasmic reductase in Campylobacter jejuni - Edward Guccione; Andrew Hitchcock; Stephen J. Hall; Francis Mulholland; Neil Shearer; Arnoud H. M. Van Vliet; David J. Kelly (Environmental Microbiology, 2010)
Summary Methylmenaquinol : fumarate reductase (Mfr) is a newly recognized type of fumarate reductase present in some ε‐proteobacteria, where the active site subunit (MfrA) is localized in the periplasm, but for which a physiological role has not been identified. We show that the Campylobacter jejuni mfrABE operon is transcribed from a single promoter, with the mfrA gene preceded by a small open reading‐frame ( mfrX ) encoding a C. jejuni ‐specific polypeptide of unknown function. The growth characteristics and enzyme activities of mutants in the mfrA and menaquinol : fumarate reductase A ( frdA ) genes show that the cytoplasmic facing Frd enzyme is the major fumarate reductase under oxygen limitation. The Mfr enzyme is shown to be necessary for maximal rates of growth by fumarate respiration and rates of fumarate reduction in intact cells measured by both viologen assays and 1 H‐NMR were slower in an mfrA mutant. As periplasmic fumarate reduction does not require fumarate/succinate antiport, Mfr may allow more efficient adaptation to fumarate‐dependent growth. However, a further rationale for the periplasmic location of Mfr is suggested by the observation that the enzyme also reduces the fumarate analogues mesaconate and crotonate; fermentation products of anaerobes with which C. jejuni shares its gut environment, that are unable to be transported into the cell. Both MfrA and MfrB subunits were localized in the periplasm by immunoblotting and 2D‐gel electrophoresis, but an mfrE mutant accumulated unprocessed MfrA in the cytoplasm, suggesting a preassembled MfrABE holoenzyme has to be recognized by the TAT system for translocation to occur. Gene expression studies in chemostat cultures following an aerobic‐anaerobic shift showed that mfrA is highly upregulated by oxygen limitation, as would be experienced in vivo . Our results indicate that in addition to a role in fumarate respiration, Mfr allows C. jejuni to reduce analogous substrates specifically present in the host gut environment.

Metagenomic analysis of stressed coral holobionts - Rebecca Vega Thurber; Dana Willner‐Hall; Beltran Rodriguez‐Mueller; Christelle Desnues; Robert A. Edwards; Florent Angly; Elizabeth Dinsdale; Linda Kelly; Forest Rohwer (Environmental Microbiology, 2009)
Summary The coral holobiont is the community of metazoans, protists and microbes associated with scleractinian corals. Disruptions in these associations have been correlated with coral disease, but little is known about the series of events involved in the shift from mutualism to pathogenesis. To evaluate structural and functional changes in coral microbial communities, Porites compressa was exposed to four stressors: increased temperature, elevated nutrients, dissolved organic carbon loading and reduced pH. Microbial metagenomic samples were collected and pyrosequenced. Functional gene analysis demonstrated that stressors increased the abundance of microbial genes involved in virulence, stress resistance, sulfur and nitrogen metabolism, motility and chemotaxis, fatty acid and lipid utilization, and secondary metabolism. Relative changes in taxonomy also demonstrated that coral‐associated microbiota ( Archaea , Bacteria , protists) shifted from a healthy‐associated coral community (e.g. Cyanobacteria , Proteobacteria and the zooxanthellae Symbiodinium ) to a community (e.g. Bacteriodetes , Fusobacteria and Fungi ) of microbes often found on diseased corals. Additionally, low‐abundance Vibrio spp. were found to significantly alter microbiome metabolism, suggesting that the contribution of a just a few members of a community can profoundly shift the health status of the coral holobiont.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)